Mosaicism for genome‐wide paternal uniparental disomy with features of multiple imprinting disorders: Diagnostic and management issues12. Issue 1 (13th December 2012) - Inbar‐Feigenberg, Michal; Choufani, Sanaa; Cytrynbaum, Cheryl; Chen, Yi‐An; Steele, Leslie; Shuman, Cheryl; Ray, Peter N.; Weksberg, Rosanna
Abstract Mosaicism for genome‐wide paternal uniparental disomy (UPD) has been reported in only seven live born individuals to date. Clinical presentation includes manifestations of multiple paternal UPD syndromes with high variability, likely due to the variable levels of mosaicism in different somatic tissues. We report an eighth case in a female patient with mosaicism for genome‐wide paternal UPD which highlights the complex clinical presentation. Our patient had features of Beckwith–Wiedemann syndrome (BWS), Angelman syndrome, and congenital hyperinsulinism. The clinical findings included prematurity, organomegaly, hemihyperplasia, developmental delay, benign tumors, and cystic lesions. The diagnosis in our patient was established utilizing microarray‐based genome‐wide DNA methylation analysis performed on leukocyte DNA. Targeted multiplex ligation‐dependent probe amplification (MLPA) analysis of chromosome regions 11p15 and 15q13 confirmed mosaicism for paternal UPD at these genomic regions. This case represents the first report of microarray‐based genome‐wide DNA methylation analysis in the diagnosis of genome‐wide paternal UPD. The application of microarray‐based genome‐wide DNA methylation analysis on selected individuals with complex clinical presentations could be a valuable diagnostic tool to improve the detection rate of mosaic genome‐wide paternal UPD. This approach, which screens many loci simultaneously, is more cost‐effective and less labor‐intensive than performing multiple targeted DNA methylation‐based assays. Identification of individuals with mosaicism for genome‐wide paternal UPD is an important goal as it confers a low recurrence risk for the family and identifies individuals who require surveillance due to increased tumor risk. © 2012 Wiley Periodicals, Inc.